The influence of plate and packed column on the mass transfer of free fatty acids from palm oil mixtures - Abdul Aziz, Mustafa Kamal; Sulong, Mohamad; Morad, Noor Azian; Lee, Thian Teck; Ayob , Azam (1989)
Stream stripping of free fatty acids from oil and splitting of oil into fatty acids are the key processes in the Malaysian Palm Oil and Oleochemicals industry. Both consumes an enormous amount of high pressure steam to provide heat and vacuum. Typically as much as 30% of the operating costs is due to steam consumption. Recently there has been a new impetus to use medium pressure and temperature to strip and split fatty acids. The study investigated the mechanisms, mass transfer rates and efficiency of the steam stripping of free fatty acids and splitting of oil to free fatty acids as well the influence of plate and packed columns scale-up on the process. The scope of the research encompassed the detremination of vapor-liquid equilibrium of oils with free fatty acids composition ranging from 2 to 7%. Bench still experiments are used to determined the mass transfer rates and efficiency of vacuum steam stripping-splitting of free fatty acids. Pilot Plant plate and Packed columns experiment were used to ascertain scale-up effects. Finally a mathemathical correlation, modelling and simulation of the experimental results were conducted and compared with computer predicted results Bench still test indicated that at low to medium operating conditions, both stripping and and splitting compete for dominance depending on the f.f.a. Driving force. The striping rate equation is a second order equation of f.f.a. stripping rate with respect to f.f.a. Driving force. This due to splitting becoming dominant as f.f.a. Driving force being reduced. On the other hand, the pilot plant plate and packed column tests indicated that at identical conditions, stripping is entirely dominant in the plate and packed columns.Futhermore, stripping rate has increased measurably and exhibit third order equation. Comparisons between plate and packed columns performaces at varying vacuum pressures indicated taht the packed column has a higher stripping rate, more steam efficient and achieved a higher level oil purity. However, the plate column reaches equilibria faster and stabilizes faster albeit over a shorter range of conditions.